Analysis of thermal-electrical performance of PVT collector with reflectors - Hanan Boulaich; Assia Benkaddour; Ouafae Hamdoun; Elhassan Aroudam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This work concerns numerical studies of PVT air collector operating in dynamic mode. We presented the temperature of the solar cells and of the air at the outlet of the PVT collector with and without reflectors. The obtained simulation results has been validated by comparating with the experimental results available in literature, where good agreement was been noted. In addition, we determine the optimal position of the reflectors by numerical calculation, in order to obtain the maximal concentration of the solar radiation intensity on PV/T collector. The thermal and electrical efficiency of PV/T collector without reflectors and with reflectors in optimal position have been calculated for composite climate at Tetouan (-5°N, 35.5°E). So, the effect of adding solar reflectors on the electrical and thermal performance is showing.